A valid and reliable method for measuring the kicking accuracy of soccer players - Finnoff, J. T.; Newcomer, K.; Laskowski, E. R. (Journal of Science and Medicine in Sport, 2002)
Kicking accuracy is an important component of soccer performance. We constructed a plywood target measuring 243.5cm wide x 122cm high. Carbon paper applied to the surface of the target allowed measurement by 2 raters from a bull's-eye to 10 ball marks left by kicks. Intraclass correlation coefficients with 95% confidence intervals were used to determine the intra- and interrater reliability of the measurement to each ball mark. Mean and median distances from bulls-eye to ball mark were 89.9cm and 97.9cm, respectively (range, 25.7 to 150.75cm). The intraclass correlation coefficients for intra- and interrater reliability were 0.99. The root mean square error of measurement indicated that accuracy of measurement was within 0.15cm. These results suggest that our method of assessing kicking accuracy is a valid and reliable tool for analysing performance. Because this tool closely replicates kicking into a soccer goal, we feel that it also has validity. To our knowledge, no other tool or measure (e.g.. number of shots on goal or number of goals per game) has comparable validity and reliability. This method can be used as a training tool and for future investigations of kicking accuracy.